The Effectiveness and Safety of Medical Cannabis for Treating Cancer Related Symptoms in Oncology Patients - Aviram, Joshua; Lewitus, Gil M.; Vysotski, Yelena; Amna, Mahmoud Abu; Ouryvaev, Anton; Procaccia, Shiri; Cohen, Idan; Leibovici, Anca; Akria, Luiza; Goncharov, Dimitry; Mativ, Neomi; Kauffman, Avia; et al. (Frontiers in Pain Research, 2022)
The use of medical cannabis (MC) to treat cancer-related symptoms is rising. However, there is a lack of long-term trials to assess the benefits and safety of MC treatment in this population. In this work, we followed up prospectively and longitudinally on the effectiveness and safety of MC treatment. Oncology patients reported on multiple symptoms before and after MC treatment initiation at one-, three-, and six-month follow-ups. Oncologists reported on the patients’ disease characteristics. Intention-to-treat models were used to assess changes in outcomes from baseline. MC treatment was initiated by 324 patients and 212, 158 and 126 reported at follow-ups. Most outcome measures improved significantly during MC treatment for most patients (p<0.005). Specifically, at six months, total cancer symptoms burden declined from baseline by a median of 18%, from 122 (82-157) at baseline to 89 (45-138) at endpoint (-18.98; 95%CI= -26.95 to -11.00; p<0.001). Reported adverse effects were common but mostly non-serious and remained stable during MC treatment. The results of this study suggest that MC treatment is generally safe for oncology patients and can potentially reduce the burden of associated symptoms with no serious MC-related adverse effects.